A responsabilidade ambiental do financiador - Santos, Guilherme Pizzotti Mendes Coletto dos (2021)
This paper will initially review the published works “Silent Spring”, by the American biologist Rachel Carson, and “Risk Society”, by the German sociologist Ulrich Beck. These published works represent the beginning of the environmental awareness movement in the world. The paper will also discuss and establish the concept of sustainable development along with a well outlined history on the subject, including the leading international conferences that focused on this matter (such as the Stockholm Conference in 1978 and the Conference of the Rio de Janeiro in 1992). The Federal Constitution and how it incorporates the ideal of sustainable development, including how it imposes on the Government the obligation to ensure that the nation's economic growth will be consistent with the necessary safeguarding of the environment, will also be addressed in this paper. Subsequently, this paper will also focus on essential principles that are inherent to the concept of sustainable development: the polluter pays principles, prevention, and precaution. This paper will also provide a study on environmental civil liability, including its most important features: its primary functions, the idea of strict liability and the theory of risks, the requirements for its characterization, the causal link in environmental civil liability, the causes for the exclusion of civil liability, such as an act of God and force majeure events, the relevance of the lawfulness condition of the activity to establish environmental civil liability, and the statute of limitations on environmental liability. Finally, this paper will discuss environmental liability from a financing viewpoint, the financier's role in light of sustainable development, and on whether and how the granting of credit facilities can be considered environmentally sustainable. The paper will then address how the North American and Brazilian case laws and the Brazilian doctrine view financiers environmental liability, and ultimately attempt to build a theory about the financial institution's environmental liability